2016
DOI: 10.1038/srep32729
|View full text |Cite
|
Sign up to set email alerts
|

Identification of SET Domain-Containing Proteins in Gossypium raimondii and Their Response to High Temperature Stress

Abstract: SET (Su(var), E(z), and Trithorax) domain-containing proteins play an important role in plant development and stress responses through modifying lysine methylation status of histone. Gossypium raimondii may be the putative contributor of the D-subgenome of economical crops allotetraploid G. hirsutum and G. barbadense and therefore can potentially provide resistance genes. In this study, we identified 52 SET domain-containing genes from G. raimondii genome. Based on conserved sequences, these genes are grouped … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
3
2

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 60 publications
(90 reference statements)
1
36
0
Order By: Relevance
“…Moreover, many SDGs were involved in high temperature responses. It can then be inferred that upon exposure to high temperature, up‐or‐downregulation of these genes might affect the status of methylation and further regulate the activity of target genes in response to high temperature …”
Section: Sdgs In Response To Stressmentioning
confidence: 99%
“…Moreover, many SDGs were involved in high temperature responses. It can then be inferred that upon exposure to high temperature, up‐or‐downregulation of these genes might affect the status of methylation and further regulate the activity of target genes in response to high temperature …”
Section: Sdgs In Response To Stressmentioning
confidence: 99%
“…This suggests that Lys methylation of histones and non-histone substrates could be part of the diverging adaptation strategies of metallicolous populations. The expression of KMT genes coding enzymes of the SDG family has been previously analyzed in cotton plants stressed with high temperature (Huang et al, 2016) and in foxtail millet under different abiotic stresses (Yadav et al, 2016). In these studies, the expression pattern of some KMT genes was significantly changed in stress conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Gene duplication, as a critical driving force, provides an extra copy of genetic material to tolerate random mutations to survive the natural selection and create new species during evolution. Gene duplication, including tandem duplication and polyploidy (whole genome duplication, WGD), considerably contributes to the formation of gene families [24], such as the SDG family in D.…”
Section: Evolution and Function Divergence Of Sdg Proteinsmentioning
confidence: 99%
“…It will be intriguing to further investigate their direct targets by highthroughput ChIP-seq method combined with excellent commercial antibodies against various histone methylation marks. Recently, Huang et al [24] thoroughly identified cotton SDG genes and noted that the expressions of most of these genes decreased under high-temperature conditions. In this study, 61% of DcSDG genes showed response to heat shock, but the number of upregulated genes was considerably higher than that of downregulated ones.…”
Section: Catenatum D Catenatum Has Undergone At Least Four Rounds Omentioning
confidence: 99%